Desain Sistem Drainase Perkotaan Sustainability dengan Pendekatan Saluran Bertingkat dan Grill Sampah di Kota Pekanbaru - Wilujeng Nugroho, Handi; Ulfa Aryani, Zakiyah (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2025)
Flooding is one of the major issues in urban areas, including in Pekanbaru City, caused by inadequate drainage systems and ineffective solid waste management. This study aims to dFlooding is one of the major issues in urban areas, including in Pekanbaru City, caused by inadequate drainage systems and ineffective solid waste management. This study aims to design an efficient, durable, and environmentally friendly urban drainage system through a tiered channel design approach equipped with trash grates. The research method used is quantitative-descriptive, consisting of literature review, field surveys, technical design using CAD software, and simulations of flow and blockage scenarios. The results show that the proposed drainage system, with a width of 100 cm, a depth of 120 cm, and a bottom slope of 0.18%, can accommodate peak discharge flows of up to 0.645 m³/s. The tiered drainage system using this garbage grill provides an increase in water flow rate of up to 35%, and reduces the potential for inundation at flood-prone points by 45%. The application of garbage grills and tiered systems has proven effective in reducing the potential for blockages and facilitating maintenance. This approach aims to achieve sustainable drainage development and adaptive flood mitigation in other urban areas. This design also supports the strategic program of the Pekanbaru City Government in flood control, and can be replicated in other cities with similar conditions.esign an efficient, durable, and environmentally friendly urban drainage system through a tiered channel design approach equipped with trash grates. The research method used is quantitative-descriptive, consisting of literature review, field surveys, technical design using CAD software, and simulations of flow and blockage scenarios. The results show that the proposed drainage system, with a width of 100 cm, a depth of 120 cm, and a bottom slope of 0.18%, can accommodate peak discharge flows of up to 0.645 m³/s. The implementation of trash grates and tiered drainage structures has proven effective in reducing blockage potential and facilitating easier maintenance. This approach is expected to support sustainable drainage development and adaptive flood mitigation in other urban areas. Additionally, the design aligns with the strategic programs of the Pekanbaru City Government in flood control and can be replicated in cities with similar conditions.